Histone acetylation modulation by a small molecule inhibitor recapitulates symbiont-induced cytoplasmic incompatibility. - Kaur, R.; Kalra, M.; Imchen, M.; Crowley, B.L.; McGarry, A.; Carpenter, L.; Bordenstein, S.R. (Cell reports, 2025)
Symbiotic relationships between arthropod hosts and microorganisms have garnered global attention for their influence on host ecology, evolution, and vector control. A major gap in the field is to mechanistically define and reconstitute symbiotic traits in the absence of microbes. Here, we address this omission by identifying an evolutionarily conserved host mechanism that recapitulates Wolbachia-induced cytoplasmic incompatibility (CI)-a paternal-effect embryonic lethality trait. We first show that Wolbachia alter histone acetylation during sperm development in Drosophila melanogaster. By chemically inhibiting histone acetyltransferase (HAT) activity in aposymbiotic males, we reprogram the chromatin landscape of developing sperm to induce a rescuable CI phenotype. This phenotype is further modulated through transgenic knockdown of HAT and histone deacetylase enzymes, providing tunable control over natural CI intensity. Our findings uncover histone acetylation as a key host-intrinsic pathway, capable of inducing symbiont-independent CI for new avenues of basic and applied studies.